Ælfric and the Cult of Saints in Late Anglo-Saxon England. By Mechthild Gretsch - Roberts, Jane (The journal of theological studies, 2007)
In her preface Gretsch explains how the beginnings of this book originated in a paper contributed to a Festschrift for Don Scragg (2002), now updated as the first chapter, ‘Ælfric's sanctorale and the Benedictional of Æthelwold’ (pp. 1–20). Shortly afterwards Scragg invited her to write about Gregory the Great for a book devoted to the popes about whom Ælfric composed lives, and the resulting paper (2001) lies behind her second chapter, ‘Gregory: the apostle of the English’ (pp. 21–64). The former paper sets up Æthelwold's Benedictional as an important context within which Ælfric's devotion to saints should be examined, the latter the approach she was to adopt for Ælfric's representation of four further saints.